Technical Challenges and Prospects for the Development of Eucheuma cottonii Seaweed Cultivation in Indonesia: A Literature Review - Ayi Yustiati; Chevrina Tri Prasetya Ningsih (Fakultas Perikanan dan Kelautan Universitas Riau, 2026)
Eucheuma cottonii is one of Indonesia’s leading seaweed commodities, possessing high economic value as a raw material for the carrageenan industry. Productivity levels in seaweed cultivation are influenced by cultivation methods, aquatic environmental conditions, and technical challenges during cultivation. This study aims to analyze the productivity of E. cottonii by considering various cultivation methods, assessing the impact of environmental factors and technical challenges on production yields, and linking these findings to the potential for the development of seaweed cultivation in Indonesia. The method used in this study is a literature review, analyzing various national and international scientific journals published between 2014 and 2025. The data analyzed included cultivation techniques, productivity levels, temperature, salinity, cultivation locations, and technical challenges affecting the growth of E. cottonii. Research findings indicate that the longline and floating raft methods generally yield higher productivity than the Off-bottom method, thanks to better water circulation, more even nutrient distribution, and higher light intensity. Environmental factors such as temperature, salinity, currents, and sedimentation influence the growth and biomass formation of seaweed. In addition, technical challenges such as ice-ice disease, changes in environmental conditions, seedling quality, and the stability of cultivation structures hinder productivity. Overall, the prospects for developing E. cottonii cultivation in Indonesia are quite promising. However, they require proper environmental management, the use of high-quality seedlings, the application of efficient cultivation technologies, and the strengthening of the downstream industry to sustainably improve productivity and increase the added value of seaweed products.